(х^2 - 1)(x+3)=0 (x^2 - 4)(x+1)=0 можно с решением, пожалуйста

0 голосов
33 просмотров

(х^2 - 1)(x+3)=0
(x^2 - 4)(x+1)=0
можно с решением, пожалуйста


Алгебра | 33 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
(х^2 - 1)(x+3)=0 значит (x^2-1)=0;(x+3)=0
                                       x^2=1     ;x=-3
                                       x=1
ответ:х=1 х=-3
(x^2 - 4)(x+1)=0 значит (x^2 - 4)=0;(x+1)=0    
                                       x^2=4       ;x=-1
                                       x=2
ответ:х=2 х=-1
(1.1k баллов)